The synergistic interaction between sulfate-reducing bacteria and pyrogenic carbonaceous matter in DDT decay. (October 2019) - Ding, Kai; Duran, Metin; Xu, Wenqing
Abstract: Although 1, 1, 1-trichloro-2, 2-di(4-chlorophenyl)ethane (DDT) was banned in the United States in 1972, it is still often detected in sediments where pyrogenic carbonaceous matter (PCM) and sulfate-reducing bacteria (SRB) co-exist. In this study, we found that 70.2 ± 0.2% of DDT disappeared in the presence of SRB and graphite powder, a model PCM, after 21 days at pH 7. Our results suggest that the observed DDT decay was due to the reaction between graphite powder and the reduced sulfur species that were produced by SRB. No biofilm formation was observed on the surface of graphite powder. Rather, the activity of SRB was inhibited by the presence of graphite powder. To understand the involvement of PCM in DDT decay, electrochemical cells and batch reactor experiments with sulfur-pretreated PCM as well as direct electrochemical reduction by a potentiostat were employed. Our results suggest that polysulfide, sulfide, sulfite, and thiosulfate could all react with PCM, forming surface-bound intermediates that subsequently led to DDT decay. The reactivity of reduced sulfur species was the highest for polysulfide, followed by sulfide, sulfite, and thiosulfate. Highlights: Pyrogenic carbonaceous matter (PCM) fostered DDT decay with sulfate-reducing bacteria. Lower toxic products were formed during the degradation process. The synergistic interaction between PCM and the biogenic sulfur species led to the DDT decay. The surface intermediates formed by reaction between sulfur species with PCM resulted in DDT decay.